2012
DOI: 10.1042/bst20110767
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic sensors and their interplay with cell signalling and transcription

Abstract: There is an intimate, yet poorly understood, link between cellular metabolic status, cell signalling and transcription. Central metabolic pathways are under the control of signalling pathways and, vice versa, the cellular metabolic profile influences cell signalling through the incorporation of various metabolic sensors into the signalling networks. Thus information about nutrients availability directly and crucially influences crucial cell decisions. In the present review, I summarize our current knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 121 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…By contrast, in Sarno, the niche of origin for the SM ecotype, a low induction of transcription and post-translational events are required. In addition, various metabolic sensing and feedback mechanisms could be able to mediate appropriate responses in crucial cellular processes, such as cell signaling, chromatin structure/function and ultimately gene expression [53]. …”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in Sarno, the niche of origin for the SM ecotype, a low induction of transcription and post-translational events are required. In addition, various metabolic sensing and feedback mechanisms could be able to mediate appropriate responses in crucial cellular processes, such as cell signaling, chromatin structure/function and ultimately gene expression [53]. …”
Section: Discussionmentioning
confidence: 99%
“…Principally, the Warburg effect reinstates how cancer cells would supplement their metabolic requirements [46, 47]. It has been shown that cancer cells exhibit heterogeneous metabolic rewiring beyond the Warburg effect suggesting that this heterogeneity is a manifestation of different metabolic adaptations by cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The seminal studies regarding CLL metabolism suggested that compared to normal lymphocytes, CLL lymphocytes consumed less glucose in a similar manner than lymphocytes from patients with diabetes mellitus [46, 47, 51, 52]. In contrast to these early studies, a recent metabolomic study using freshly isolated CLL lymphocytes revealed that these malignant lymphocytes display high levels of aerobic glycolysis and produce lactate which are consistent with the use of glucose and the Warburg effect [53].…”
Section: Discussionmentioning
confidence: 99%
“…Warburg reasoned that respiration must be damaged in cancers because high levels of O 2 are unable to suppress the production of lactic acid by cancer cells (known as the Pasteur effect). However, new studies have demonstrated that tumor mitochondria are fairly functional with regards to respiration and ATP synthesis, exhibiting almost normal respiratory control ratios and capabilities for the oxidation of respiratory substrates (Bensinger and Christofk 2012; Eakin, et al 1972; Krejci 2012; Nakajima and Van Houten 2012). …”
Section: Introductionmentioning
confidence: 99%